Evaluation of Gum‐line Recession for Aging Lynx (Lynx canadensis). (8th December 2021) - Peers, Michael J. L.; Majchrzak, Yasmine N.; Studd, Emily K.; Menzies, Allyson K.; Kukka, Piia M.; Konkolics, Sean M.; Boonstra, Rudy; Boutin, Stan; Jung, Thomas S.
ABSTRACT: Accurate age estimates of wildlife are important for both research and management purposes. Despite the value of determining the age of individuals, cost effective and minimally‐invasive approaches are lacking for most species. Assessment of gum‐line recession is a minimally‐invasive, cost‐effective method used for aging some felids; however, its reliability is unknown. Here, we evaluate the utility of gum‐line recession for aging Canada lynx ( Lynx canadensis ), using carcasses collected during the winters of 2015–2016 and 2016–2017 from trappers in Yukon, Canada. The purpose of our study was to 1) assess the repeatability of measuring gum‐line recession within and between observers, 2) compare measurements of gum‐line recession to estimates of age obtained from cementum annuli analysis, and 3) test for differences in mean gum‐line recession between age‐classes of lynx (i.e., young, prime adult, and old adults). We found that although estimated gum‐line recession was repeatable within an observer, it was not between observers, and did not correlate strongly with estimated age based on cementum annuli. Significant differences in mean gum‐line recession were found between age classes. We conclude that gum‐line recession does not provide an accurate estimate of age in Canada lynx and that other methods would be required if tooth extraction is not desirable. However, gum‐line recession may be useful for determining age class of lynx. Finally, we recommend similar assessments of precision and observer bias when measuring gum‐line recession to estimate the age of other species. © 2021 The Wildlife Society. Abstract : Indices of individual age are valuable for many studies; however, they require validation prior to their use. We found that gum‐line recession—a method commonly used to age felids—does not correlate strongly with cementum‐based age estimates of Canada lynx ( Lynx canadensis ) but may be useful for sorting animals by age‐class. We urge consideration of observer bias when using gum‐line recession to estimate age.